PENGARUH LINGKUNGAN BELAJAR TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN PENGANTAR EKONOMI DAN BISNIS KELAS X AKUNTANSI DI SMK NEGERI 4 KOTA JAMBI - Benar Sembiring, Rissa Stepani Sitinjak, (SJEE (Scientific Journals of Economic Education), 2018)
Abstract This study aims to determine the description of respondents and the influence of learning environment on student learning outcomes on introductory subjects of economics and business class X accounting in SMK Negeri 4 Kota Jambi. Based on the data analysis on the results of research that there is a significant influence between the learning environment on student learning outcomes in the introductory subjects of economics and business class X accounting in SMK Negeri 4 Kota Jambi. With result of model summary R = 0,593 and R Square = 0,352. Because α (Sig) <0.05, then regression can be used to predict the learning environment at 95% confidence level. In coefficient B constant value = 4.893, states that if teacher professionalism variable is ignored, then teacher's performance = 4,893. Meanwhile, the value of the variable for the learning environment (X) is 0.379, stating that if the level of learning environment as involved, then the student learning outcomes increase around 0.379. Keyword : Learning Environment, Learning Outcomes.